Histopathological features of Marekâs disease infections in broiler chicken in Districts of Tasikmalaya and Ciamis West Java - Damayanti, R; Wiyono, A (Indonesian Animal Sciences Society, 2003)
An outbreak of Marekâs disease was reported to occur in broiler chicken in Districts of Tasikmalaya and Ciamis. A total number of 58 tissues samples of broiler chicken were collected from 7 flocks of commercial broiler chicken farms in both Districts. The disease affected broiler chicken aged 17 to 24 days. Those chickens had been vaccinated to Newcastle Disease (ND) and at age of 10 days had been vaccinated to Gumboro using blended bursa of fabricius. Tissue samples were fixed in 10% of buffered neutral formalin (BNF) prior to haematoxilin and eosin (H and E) stain using standard procedures. Histopathological features show that out of 58 samples, 32 (55.2%) were infected by Marekâs Disease (19.0% were infected by Marekâs Disease, 20.1% were infected by Marekâs Disease and Gumboro, 16.1% Marekâs Disease and other infections), whereas 44.8% were infected by Gumboro alone or accompanied by other infections, ND and Colibasillosis. The study reveals that Marekâs Disease infection in broiler chicken tends to be mild i.e. infiltration of neoplastic cells (lymphoid, pleomorphic) in proventriculus, intestine, spleen, livers and bursa of fabricius. In addition to this, there were mild non-supurative inflammation in heart, lung, peripheral nerve and brain, as well as a severe demyelination in brain. It is concluded that the histopthological features confirm the diagnosis of Marekâs Disease. Â Key words: Histopathology, Marekâs disease, broiler chicken, Districts of Tasikmalaya and Ciamis (West Java)